Professional And Ethical Influences on the Accounting Profession - Hasmi, Nurul; Winda, Winda; Ongku, Sartina Abd R.; Hasan, Septianti D. Sinta; R, Desak Ayu Kompyang; Budiawan, Shella (Amsir Accounting & Finance Journal, 2024)
Every profession providing services to the public must have a code of ethics, a set of moral principles that govern professional behaviour. This study aims to determine how professional and ethical influences the accounting profession. The method in this research is to use a literature review by using secondary data, namely from literature studies through scientific articles, research journals and Google Scholar. The results of this study indicate that of the eight articles used in this literature review, 7 have a significant relationship or influence between professional behaviour and the ethics of the accounting profession, including public accountants, teaching accountants, auditor professionals, forensic accountants, and tax consultants. Everything is related to professional behaviour to support the achievement of professional responsibility properly, especially in accounting.